The impact of electronic payments on the trading volume index in the Iraq Stock Exchange (Entrepreneurship Journal for Finance and Business, 2025)
Research and studies related to electronic payments and the indicators of the Iraq Stock Exchange hold significant importance as they represent one of the fundamental elements contributing to economic progress. This research aims to measure the impact of electronic payments on the trading volume index in the Iraq Stock Exchange. To achieve this goal, the unit root will be tested using the Augmented Dickey-Fuller test and the Phillips-Perron test, and cointegration will be tested using the) ARDL (model according to the outputs of the) Eviews13(econometric software. The research concluded that there is a positive relationship between electronic payment indicators (amounts of electronic checks, value of bank transfers, retail payment system transfers) and the trading volume index in the Iraq Stock Exchange. The research recommends enhancing online electronic trading to help investors quickly identify trading indicators and stock prices of listed companies, which leads to increased trading activity in the Iraq Stock Exchange. This can be achieved by organizing workshops and educational seminars to provide detailed information on modern technologies used in the market